The human resource management of political staffers insights from Prime Ministers' advisers and reformers - Lees-Marshment, Jennifer (Routledge, Taylor & Francis Group, 2024)
"The Human Resource Management of Political Staffers: Insights from Prime Ministers' Advisers and Reformers explores the human resource management of political staffers and advisers who work for politicians. Deeply grounded in the experiences of those who worked in the highest political offices under Prime Ministers Boris Johnson, Justin Trudeau, Scott Morrison and Jacinda Ardern, it makes the case for better management of staffers by illuminating past problems with the workplace such as extreme workloads, little work-life balance and lack of orientation and training. But it also offers a way forward by combining ad hoc positive experiences into guidance for future best practice. Drawing on interviews with advisers/staffers and practitioners working on HR reform in politics, in four countries - the UK, Canada, Australia and New Zealand - it provides a research-informed best practice guide for the staffers/advisers, their managers and reformers which offers practical advice on how to recruit, orientate and train, manage and support staffers and advisers appropriately within the complex political environment. It also conveys the highly skilled roles staffers undertake and the democratic contribution they make. The Human Resource Management of Political Staffers is a must-have guide to current and future advisers, politicians and ministers. Human Resource Management for political staffers is important not just for the individuals but to enable taxpayer-funded staffers to perform more effectively, which will in turn help elected politicians deliver for voters."
Keywords: Commonwealth; Politischer Berater; Humanvermögen; Personalentwicklung; Executive departments / Commonwealth countries / Personnel management; Administrative agencies / Commonwealth countries / Personnel management; Commonwealth countries / Officials and employees; Cabinet system / Commonwealth countries; Political consultants / Commonweath countries